AKUNTANSI DAN DAKWAH - Uswatun Hasanah; Oppie Meisya Tanjung (JURNAL SYIAR-SYIAR, 2023)
Dawah organizations often face complexity in financial structures, involved in collecting and distributing funds from various sources, and utilizing them for various dawah and humanitarian programs. Careful financial management and proper accounting are crucial to ensure efficiency and transparency in fund utilization. Openness and transparency are also crucial to maintaining donor trust. This research aims to understand the importance of integrating accounting in dawah to achieve dawah goals more effectively and efficiently. The method used is a literature review. The research indicates that implementing strong accounting practices can provide clear and detailed financial reports, meeting the need for transparency in financial management. By integrating accounting into dawah, organizations can improve the effectiveness and efficiency of fund management, ensuring that funds are used for the promised purposes. In conclusion, the integration of accounting into dawah is a crucial step in achieving dawah goals better and maintaining integrity in financial management.